Evaluating official development assistance-funded granting mechanisms for global health and development research that is initiated in high-income countries - Adèle Cassola; Prativa Baral; John-Arne Røttingen; Steven J. Hoffman (BMC, 2022)
Abstract Background Several countries allocate official development assistance (ODA) for research on global health and development issues that is initiated in the donor country. The integration of such research within domestic research systems aligns with efforts to coordinate ODA investments with science, technology and innovation policies towards achieving the Sustainable Development Goals (SDGs). Methods Through a document synthesis and interviews with research funders in ODA donor and recipient countries, we evaluated the performance of this funding approach across seven donor-country programmes from five donor countries and examined the institutional design elements that increase its chances of advancing development goals and addressing global challenges. Results We found that carefully designed programmes provide a promising pathway to producing valuable and contextually relevant knowledge on global health and development issues. To achieve these outcomes and ensure they benefit ODA-receiving countries, programmes should focus on recipient-country priorities and absorptive capacity; translate research on global public goods into context-appropriate technologies; plan and monitor pathways to impact; structure equitable partnerships; strengthen individual and institutional capacity; and emphasize knowledge mobilization. Conclusions Global health and development research programmes and partnerships have an important role to play in achieving the SDGs and addressing global challenges. Governments should consider the potential of ODA-funded research programmes to address gaps in their global health and development frameworks. In the absence of concrete evidence of development impact, donor countries should consider making increases in ODA allocations for research additional to more direct investments that have demonstrated effectiveness in ODA-receiving countries.